2017
DOI: 10.1038/ncomms16000
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Adenylate kinase hCINAP determines self-renewal of colorectal cancer stem cells by facilitating LDHA phosphorylation

Abstract: The original version of this Article contained an error in the spelling of the author Zemin Zhang, which was incorrectly given as Zeming Zhang. This has now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…LDHA is phosphorylated at tyrosine 10 (Y10) by oncogenic receptor tyrosine kinase FGFR1, which facilitates the formation of active LDHA tetramers (Fan et al, 2011). FGFR1catalyzed LDHA phosphorylation can be enhanced by adenylate kinase hCINAP to augment the catalytic activity of LDHA (Ji et al, 2017). LDHA can also be acetylated and recognized by HSC70, which then delivers LDHA to lysosome to be degraded (Zhao et al, 2013).…”
Section: Lactate Dehydrogenasementioning
confidence: 99%
“…LDHA is phosphorylated at tyrosine 10 (Y10) by oncogenic receptor tyrosine kinase FGFR1, which facilitates the formation of active LDHA tetramers (Fan et al, 2011). FGFR1catalyzed LDHA phosphorylation can be enhanced by adenylate kinase hCINAP to augment the catalytic activity of LDHA (Ji et al, 2017). LDHA can also be acetylated and recognized by HSC70, which then delivers LDHA to lysosome to be degraded (Zhao et al, 2013).…”
Section: Lactate Dehydrogenasementioning
confidence: 99%
“…According to these studies, both overexpressed and endogenous hCINAP showed an obvious nuclear localization. In addition, biochemical approaches such as subcellular fractionation have been employed to examine the localization of endogenous hCINAP [14–16]. These subcellular fractionation assays showed that endogenous hCINAP is localized in both the cytosol and the nucleus.…”
Section: Hcinap/ak6 Is An Atypical Adenylate Kinasementioning
confidence: 99%
“…Ji et al . [14] identified hCINAP as a potent modulator of metabolic reprogramming in colorectal cancer (CRC) stem cell (CRCSC) proliferation, invasion and metastasis. Mechanistically, hCINAP binds to the C‐terminal domain of LDHA, a key glycolysis regulator, and regenerates ATP to promote fibroblast growth factor receptor 1‐catalyzed LDHA phosphorylation in an AK activity‐dependent manner.…”
Section: Hcinap/ak6 Functions In Important Signaling Pathways and Cellular Processesmentioning
confidence: 99%
See 2 more Smart Citations